2018
DOI: 10.1097/sih.0000000000000293
|View full text |Cite
|
Sign up to set email alerts
|

The 100 Most Cited Articles on Healthcare Simulation

Abstract: This article provides an overview and synthesis of the 100 most cited healthcare simulation publications to provide insight into the articles that have shaped current knowledge and practice. Searches of the Scopus and Web of Science databases were conducted in July 2017. Most articles were concerned with medical education and training (86%) and were most often published in surgical journals (33%). Manikins (20%), standardized patients (16%), inanimate part-task trainers (16%), fully simulated environments (17%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 123 publications
(162 reference statements)
1
28
1
Order By: Relevance
“…Half of the articles (n=25) on the top-cited list were by authors in the U.S., followed by the United Kingdom and Greece. This finding is similar to the results of bibliometric studies in health care simulation education, medical education, and dental education, which also found the majority of articles originated in the U.S. [15][16][17] The U.S. authors of these articles were at eight universities, so no single institution could be ranked highest on the contributing institutions list. On the other hand, the institution with the largest number of articles on the top-cited list was the University of Athens in Greece, and all four of these articles were by authors from the same institution.…”
Section: Figure 2 Countries Of First Authors Of Top-cited Articlessupporting
confidence: 84%
See 3 more Smart Citations
“…Half of the articles (n=25) on the top-cited list were by authors in the U.S., followed by the United Kingdom and Greece. This finding is similar to the results of bibliometric studies in health care simulation education, medical education, and dental education, which also found the majority of articles originated in the U.S. [15][16][17] The U.S. authors of these articles were at eight universities, so no single institution could be ranked highest on the contributing institutions list. On the other hand, the institution with the largest number of articles on the top-cited list was the University of Athens in Greece, and all four of these articles were by authors from the same institution.…”
Section: Figure 2 Countries Of First Authors Of Top-cited Articlessupporting
confidence: 84%
“…Surveys were the main research method used in the majority of articles on our top‐cited list. This finding was different from those of bibliometric studies on medical education and health care simulation education and research which found reviews had the highest number of citations 17 , 25 . Reviews are especially useful to the development of scholarship because they give researchers an overview of the currently available evidence.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Current practice for surgical training has moved away from traditional methods of practicing and teaching on live patients. Novel methods of teaching trainees including simulation are increasingly being incorporated into surgical curricula and literature in an attempt to improve patient safety . Simulation based learning has shown promise in reducing error rates and improving time to achieving proficiency in surgical skills.…”
Section: Introductionmentioning
confidence: 99%